Distortions to Agricultural Incentives in Australia Since World War II - Anderson, Kym; Lloyd, Peter; MacLaren, Donald (World Bank, Washington, DC, 2012)
Australia's lackluster economic growth performance in the first four decades following World War II was in part due to an anti-trade, anti-primary sector bias in government assistance policies. This paper provides new annual estimates of the extent of those biases since 1946 and their gradual phase-out during the past two decades. In doing so it reveals that the timing of the sector assistance cuts was such as sometimes to improve but sometimes to worsen the distortions to incentives faced by farmers. The changes increased the variation of assistance rates within agriculture during the 1950s and 1960s, reducing the welfare contribution of those programs in that period. Although the assistance pattern within agriculture appears not to have been strongly biased against exporters, its reform has coincided with a substantial increase in the export orientation of many farm industries. The overall pattern for Australia is contrasted with that revealed by comparable new estimates for other high-income countries.